Neural signatures of extreme sensitivities to light: cortical markers in hypersensitive and hyposensitive individuals via EEG - Salvati, Valerio; Otani, Satoru; Tartaglia, Elisa M. (Frontiers in Neuroscience, 2025)
Light plays a crucial role in human biology. However, while the general pathways involved in light perception are well-understood, the specific neural mechanisms explaining why some individuals experience an adverse behavioral response to light (hypersensitivity), while others rather the opposite (hyposensitivity) remain unclear. Here, leveraging the high temporal resolution of EEG, we set out to test the hypothesis that, in hyposensitive individuals, an excessive sensory stimulation may lead to neural hyper-excitability. Such an enhanced response, in turn, might be key to mitigate discomfort. We conducted our study on 21 participants, who underwent light exposure tests at varying intensities. Our findings revealed that hyposensitive individuals, who are less averse to intense light exposure, can rely on a more efficient neuroprotective mechanism against sensory overload, when compared to hypersensitive individuals. Such a mechanism is mainly and consistently expressed through the increase in power of beta and gamma oscillations, along with a delayed onset of the P100 component in response to light stimuli. These findings open the door for future research to adaptive technologies that utilize EEG markers to create personalized, real-time interventions for light sensitivity, such as adaptive wearable devices or environmental systems that dynamically adjust lighting based on neural feedback, providing immediate relief for hypersensitive individuals.